PENERAPAN KEGIATAN KOLASE DAN MOZAIK UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK AN NURAISYAH DESA AJALASSE KECAMATAN CENRANA KABUPATEN BONE - WIWI SAFITRI; Hasan Basri; Sitti Fatimah (Institut Agama Islam Negeri Bone, 2026)
Fine motor development is a crucial aspect of early childhood development, influencing their ability to perform daily activities, such as writing, drawing, and operating small tools. In children aged 4–5, fine motor skills are still developing and require appropriate stimulation to optimize their abilities. At An Nuraisyah Kindergarten, several children exhibited delays in fine motor development, particularly in activities requiring hand-eye coordination, such as tearing, sticking, and holding writing instruments. This study aimed to examine the effect of collage and mosaic activities on the fine motor development of 4–5-year-old children at An Nuraisyah Kindergarten. Before treatment, the children exhibited delays in fine motor skills, particularly in activities involving hand-eye coordination, such as tearing, sticking, and holding writing instruments. This study used an experimental design with a pretest-posttest method, involving 19 children. The pretest results showed an average fine motor skill of 32.21, reflecting limited manipulative skills in the early stages. After being given collage and mosaic activities, there was a significant increase in children's fine motor skills, with an average post-test score of 79.68. Data normality tests indicated a normal distribution, while homogeneity tests and t-tests revealed statistically significant differences (Sig. <0.05). These findings indicate that collage and mosaic activities can be an effective learning strategy for optimally stimulating fine motor development in early childhood. The results of this study provide an important contribution to the development of more enjoyable and targeted learning methods for children in early childhood education. Keywords: fine motor skills, collage, mosaic, early childhood, creative learning, child development, hand-eye coordination.